Association between dietary patterns and sarcopenia among community-dwelling older adults in five provinces of China: a cross-sectional study - Pu, Rongchang; Jia, Shanshan; Zhang, Xiaona; Man, Qingqing; Yu, Dongmei; Cai, Shuya; Song, Pengkun; Zhang, Jian (Frontiers in Public Health, 2025)
BackgroundSarcopenia is prevalent in older adults and not only severely affects their health, but also brings a greater economic burden on the patient’s family as well as society. High-quality diet is one of influencing factors of sarcopenia, particularly important for muscle mass and function. This study aims to examine the dietary patterns of community-dwelling older adults in a typical region of China and explore the relationship between these dietary patterns and sarcopenia.MethodsWe used data of the Nutrition and Health Follow-up Study of the Chinese Population in 2021. Food frequency questionnaires were used to obtain food items intake frequency during the last year. Appendicular skeletal muscle mass (ASM), muscle strength and physical performance were assessed according to the Asian Sarcopenia Working Group (AWGS2019) criteria. Exploratory factor analysis was used to identify dietary patterns. Logistic regression models were used to examine the association between dietary patterns and sarcopenia.ResultsA total of 1,967 participants over the age of 65 were included in the study, and the prevalence of sarcopenia was 17.0%. According to the factor loadings of all of the 18 food groups, three dietary patterns were identified. These dietary patterns include the diversified dietary pattern, which is mainly characterized by the intake of soybeans, fungi and algae, animal meat, fruits, and legumes; the traditional dietary pattern, which is mainly defined by the consumption of rice, pork, poultry, vegetables, and aquatic products; and the wheat-based dietary pattern, which is mainly characterized by the intake of wheat, tubers, and other cereals. The diversified dietary pattern (OR = 0.54, p < 0.05) and the traditional dietary pattern (OR = 0.51, p < 0.05) were linked to a lower risk of developing sarcopenia, whereas the wheat-based dietary pattern (OR = 3.54, p < 0.05) was associated with a higher risk of sarcopenia. All three dietary patterns exhibited significantly correlated with muscle mass, grip strength, and physical performance (p < 0.05).ConclusionDietary patterns are associated with sarcopenia in community-dwelling older adults in China. Adopting a healthy and sensible balanced diet and avoiding a single dietary preference may reduce the risk of sarcopenia in older adults.